Evaluación de dos abonos orgánicos sobre el rendimiento del cultivo de coliflor (Brassica oleracea) en la zona de Mocache. - Manosalvas Cevallos, Adrián Raúl (2016)
In Ecuador, 900 ha-1 of cauliflower is cultivated, with a yield of 11637 MT, and a national average yield of 12.93 TM / ha-1, now showing that its demand has increased locally as well as internationally. This vegetable stands out for its important benefits and properties that it possesses for health. The objective of this research was to evaluate the effect of the application of two organic fertilizers (compost, humus), at different levels of application in the cultivation of cauliflower (Brassica oleracea). The present investigation was carried out during the period from July to 2015, in the Canton Mocache in a plot located in the sector of the prairies owned by Don Carlos Manosalvas, whose geographic coordinates are: 79 ° 27 'long or east and 01 ° 06 'south latitude at an altitude of 73 masl. The factors under study were A. organic vouchers (Humus Compost) B. Dose (High 15 t ha-1, Medium 10 t ha-1, Low 5 t ha-1 and 5 t Compost + 5 t Humus ha-1). The main results were the T5 treatment in high doses (Humus 15 t ha-1) which achieved the highest yields in this study with 30250.4 kg ha -1; Followed by the treatment comprising the combination (compost 5 t ha-1 + humus 5 t ha-1) with a yield of 24726.4 kg ha -1 which despite its application was lower in tonnes per hectare A significant performance. In contrast to the treatment T1 (absolute control) that obtained the lowest yield per hectare with 11574.1 kg. Key words: Organic fertilizer, Cauliflower, Compost, Humus